1955
DOI: 10.2337/diab.4.4.290
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Disease in the Diabetic

Abstract: More than half of the deaths in the United States today are due to cardiovascular renal diseases, and chief among these is coronary heart disease. Among diabetics this complication is particularly common. Of 3,499 deaths among patients of the Joslin Clinic between Jan. I, 1944, and Apr. 27, 1951, 2,456, or 70.2 per cent, were considered by the attending physician to be due to arteriosclerotic cardiovascular-renal disease. Of the total deaths 1,627, or 46.5 Per cent, were ascribed to arteriosclerotic heart dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1960
1960
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…A secondary analysis from the UKPDS showed an adjusted rate of heart failure of 2.3 events/100 person-years among patients with HbA 1c levels of <6% compared to 11.9 among those with HbA 1c levels >10%. 30 Among 48,858 patients with predominantly type 2 diabetes, each 1% increase in HbA 1c is associated with an 8% increased relative risk of heart failure; 9 a similar relationship has been observed among 20,985 patients with type 1 diabetes (30% increased relative risk of heart failure per 1% increase in HbA 1c ). 506 …”
Section: Role Of Glycemic Controlmentioning
confidence: 72%
See 1 more Smart Citation
“…A secondary analysis from the UKPDS showed an adjusted rate of heart failure of 2.3 events/100 person-years among patients with HbA 1c levels of <6% compared to 11.9 among those with HbA 1c levels >10%. 30 Among 48,858 patients with predominantly type 2 diabetes, each 1% increase in HbA 1c is associated with an 8% increased relative risk of heart failure; 9 a similar relationship has been observed among 20,985 patients with type 1 diabetes (30% increased relative risk of heart failure per 1% increase in HbA 1c ). 506 …”
Section: Role Of Glycemic Controlmentioning
confidence: 72%
“…The high prevalence of coronary and peripheral artery disease in individuals with diabetes has been recognized for over a century, 7–9 yet the ability to improve cardiovascular event rates by glucose lowering per se has remained elusive. In the landmark Framingham Heart Study published in 1979, Kannel and McGee first prospectively demonstrated a higher incidence of cardiovascular disease across all age groups for individuals with diabetes (defined at the time by random blood glucose of ≥150 mg/dL [8.3 mmol/L]) compared to those without, with an even greater impact of diabetes on cardiovascular morbidity and mortality for women than for men.…”
Section: Epidemiology Of Ascvd In Diabetesmentioning
confidence: 99%
“…Clinical [1,2,3] and pathological [4] studies testify to the frequency of cardiovascular (CV) complications in diabetes, particularly since the increased longevity following the introduction of insulin and antibiotics. Almost 20 years after the introduction of the oral hypoglycaemic agents this still holds true [5].…”
mentioning
confidence: 99%
“…Four of the patients had had the diagnosis of diabetes made at age fifteen or earlier. Interestingly, peripheral vascular affliction resembles coronary artery disease, which occurs about as commonly in diabetic women as in men 11 ; the slight excess of women equals female diabetic preponderance past the middle decades of life. This, and tobacco restriaions advocated in diabetic clinics may account for only thirty-seven male and eleven female regular smokers in our series (female and male smokers alike presenting the average arterial status for our 143 patients).…”
Section: Clinical Resultsmentioning
confidence: 99%